Strategic Management Workshop for Early Childhood Teachers In the Era of Independent Curriculum - Bendriyanti, Rita Prima; Mayasari, Henni; Fadilla, Rohayu; Nurwita, Syisva (Indonesia Berdaya, 2025)
The transformation of Indonesian education through the Merdeka Curriculum has the consequence of the need to strengthen the competence of educators, including Early Childhood Education (ECED) teachers. Teachers are no longer just teachers, but also learning leaders who are required to be able to manage the learning process strategically. This strategic management workshop was organized as a form of community service to equip PAUD teachers with understanding and skills in developing, implementing, and evaluating learning in a planned and adaptive manner. The results of the activity show an increase in teacher competence in applying strategic management principles according to the characteristics of early childhood and the demands of the Merdeka Curriculum.